Analysis of Soil Tability and Foundation of Berbah Sleman SPAM Water Tank Using Plaxis with Soil Results Cone Pentrasion Test (CPT) - Muhammad Abdu; Aswad Asrasal; Idwan Idwan; Fahmi Fahmi (Civil Engineering Faculty, Universitas Muhammadiyah Buton, 2022)
Berbah is a subdistrict in the sleman regency of the special region of Yogyakarta with a total of 52565 people with this large population, so the use of clean water is very important for survival so that facilities and infrastructure to meet clean water needs must be provided in the hope that the needs of the community can be achieved. One of the facilities and infrastructure to achieve these needs requires a management place or water reservoir in the form of a water tank with a capacity based on the needs of the community. One of the tanks made in the berbah sub-district area is 10x10m with a tank height of 3.8m with a target capacity of 300 m3. Based on analysis with soil data Cone Penetration test (CPT) with 2D modeling in plaxis with water loading and gradually analyzed obtained under modeling conditions without water load, there was a decrease with t = 1 day of 1.319 with SF = 9.205 mm and when weighed for t = 30 days experienced an additional decrease of 0.008mm S = 1.327 mm and for t = 30 it was in a condition of no longer decreasing until the next With SF = 9.19. So it can be concluded that the foundation used can use the foundation from the bottom of the tank itself.